2018
DOI: 10.1136/oemed-2018-105269
|View full text |Cite
|
Sign up to set email alerts
|

Tunnel driving occupational environment and hearing loss in train drivers in China

Abstract: ObjectiveHearing loss caused by high levels of noise is a potential occupational health disorder among train drivers around the world. This study aims to investigate the relationship between tunnel driving occupational environment and hearing loss in train drivers, to provide some insights into helping reduce hearing loss among train drivers.MethodsThis study analysed cross-sectional data for 1214 train drivers who work at China Railway Guangzhou Group. Health examination was taken by physicians with professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 24 publications
1
20
0
1
Order By: Relevance
“…This is roughly in line with an earlier study that reported maximum noise exposure levels between 70 and 80 dBA for locomotive engineers in Norway (Lie et al 2013). Higher maximum noise levels were measured in Chinese trains, varying from 88 to 93 dBA (Peng et al 2019). The significant effect of train type and driving speed on the noise level confirmed the results of Kurze et al (2000) and Pronello (2003).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is roughly in line with an earlier study that reported maximum noise exposure levels between 70 and 80 dBA for locomotive engineers in Norway (Lie et al 2013). Higher maximum noise levels were measured in Chinese trains, varying from 88 to 93 dBA (Peng et al 2019). The significant effect of train type and driving speed on the noise level confirmed the results of Kurze et al (2000) and Pronello (2003).…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, the background noise at each workplace should be taken into account, including the level, spectrum, and type of the noise (Edworthy 1994;Gigu ere et al, 2008). A train cabin is a noisy working environment with A-weighted estimated noise levels between 70 and 93 dBA (Lie et al 2013;Peng et al 2019). Driving speed can influence the ambient noise level, since the overall exterior sound emission increases with driving speed and several of the internal noise sources depend on driving speed, such as the motor and cooling ventilator (Kurze, Diehl, and Weißenberger 2000;Pronello 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The fast transient pressure changes experienced in high-speed trains when passing through tunnels [10] are associated with aural discomfort [11], can attenuate sound transmission through the outer and middle ear [12] and have thus the potential to interfere with speech intelligibility. Repeated tunnel passing has even been linked to persistent hearing loss in train drivers [13], though the primary concern here was tunnel noise. In general, negative middle ear pressure is a common pathological dysfunction and has been intensely studied [14].…”
Section: Introductionmentioning
confidence: 96%
“…In recent years, one of the most important goals in the automotive industry has been to offer passengers the highest level of safety, comfort, and efficiency by partially or completely removing driving duties from humans. Advanced Driver Assistant System (ADAS) has become a research hotspot in the field of intelligent transportation; it not only improves the road capacity [1], but also ensures the safety of drivers and vulnerable road users to some extent [2,3]. Studies have shown that the active safety systems, such as adaptive cruise control, electronic stability control, or lane keeping assistant, which are already on the automotive market, can improve safety by decreasing the number of traffic accidents, among which the ACC helps a lot to reduce the driver's work intensity; an ACC equipped vehicle uses radar or other sensors that detect the distance and speed to other preceding vehicles (downstream vehicles) on the highway.…”
Section: Introductionmentioning
confidence: 99%